A novel simulated multilevel inverter topolo-gy with minimal switches - Anand, R.; Muthu Balaji, S. (International Journal of Engineering and Technology, 2017)
In this project, an advanced design of simulated multilevel inverters is proposed, which helps to boost the number of output voltage levels and decrease the number of power switches, driver circuits, and the maximum charge of the inverter. It is significant to note down advanced design, the unidirectional power switches are used. Results in decreased complexity and economical. The comparison is done with the conventional topologies and confirmed by simulation outcome. The planned design by using the new technique in produce all voltage levels for a stage inverter which its performance and functional accuracy is confirmed by simulation and experimental results.